Potential skin irritation of Tay Son Tam Kiet herbal spray in rabbits - Anh, Pham Thi Van; Thuy, Nguyen Thi; Quynh, Nguyen Thi Nhu; Huong, Pham Thi Thanh; Ngoan, Dao Thi; Duong, Dau Thuy (Tạp chí Nghiên cứu Y học, 2026)
Tay Son Tam Kiet herbal spray (TSTK) is a traditional external preparation composed of several medicinal herbs and minerals, including Rhizoma Rhei, Flos Carthami, Ramulus Cinnamomi, Natrium Sulfuricum, Gummi resina Olibanum, Acacia catechu, Rhizoma Bletillae striatae, Sanguis Draconis, Aloe vera, Radix Astragali membranacei, and Radix Paeoniae lactiflorae with the intended use to relieve musculoskeletal pain, swelling, and bruising. To provide preclinical safety information, this study aimed to evaluate its dermal irritation potential in experimental animals. In this study, 0.5 ml of TSTK was applied to one side of the dorsal skin of rabbits, while 0.5 ml of distilled water was applied on the opposite side as a normal control. Both sites were covered with gauze and fixed for 4 hours. The erythema and edema were scored at 1h, 24h, 48h and 72h post-removal. Results showed that no erythema, edema, or other skin lesions were observed in all rabbits at any time point. According to the Organisation for Economic Co-operation and Development (OECD) Test Guideline 404 and the International Organization for Standardization (ISO) classifications, the TSTK herbal spray did not cause skin irritation in rabbits. These results support its safety for further development and clinical application.